Cardioprotection induced by a brief exposure to acetaldehyde: role of aldehyde dehydrogenase 2. Issue 7 (20th March 2018) - Ueta, Cintia Bagne; Campos, Juliane Cruz; Albuquerque, Rudá Prestes e; Lima, Vanessa Morais; Disatnik, Marie-Hélène; Sanchez, Angélica Bianchini; Chen, Che-Hong; de Medeiros, Marisa Helena Gennari; Yang, Wenjin; Mochly-Rosen, Daria; Ferreira, Julio Cesar Batista
Abstract: Aims: We previously demonstrated that acute ethanol administration protects the heart from ischaemia/reperfusion (I/R) injury thorough activation of aldehyde dehydrogenase 2 (ALDH2). Here, we characterized the role of acetaldehyde, an intermediate product from ethanol metabolism, and its metabolizing enzyme, ALDH2, in an ex vivo model of cardiac I/R injury. Methods and results: We used a combination of homozygous knock-in mice (ALDH2*2), carrying the human inactivating point mutation ALDH2 (E487K), and a direct activator of ALDH2, Alda-1, to investigate the cardiac effect of acetaldehyde. The ALDH2*2 mice have impaired acetaldehyde clearance, recapitulating the human phenotype. Yet, we found a similar infarct size in wild type (WT) and ALDH2*2 mice. Similar to ethanol-induced preconditioning, pre-treatment with 50 μM acetaldehyde increased ALDH2 activity and reduced cardiac injury in hearts of WT mice without affecting cardiac acetaldehyde levels. However, acetaldehyde pre-treatment of hearts of ALDH2*2 mice resulted in a three-fold increase in cardiac acetaldehyde levels and exacerbated I/R injury. Therefore, exogenous acetaldehyde appears to have a bimodal effect in I/R, depending on the ALDH2 genotype. Further supporting an ALDH2 role in cardiac preconditioning, pharmacological ALDH2 inhibition abolished ethanol-induced cardioprotection in hearts of WT mice, whereas a selective activator, Alda-1, protected ALDH2*2 against ethanol-induced cardiotoxicity. Finally, either genetic or pharmacological inhibition of ALDH2 mitigated ischaemic preconditioning. Conclusion: Taken together, our findings suggest that low levels of acetaldehyde are cardioprotective whereas high levels are damaging in an ex vivo model of I/R injury and that ALDH2 is a major, but not the only, regulator of cardiac acetaldehyde levels and protection from I/R.